2018
DOI: 10.12984/egeefd.396759
|View full text |Cite
|
Sign up to set email alerts
|

Ergen-Ebeveyn Kariyer Uyumu Ölçeği'ni Türkçeye Uyarlama Çalışması

Abstract: Bu araştırmanın temel amacı Ergen-Ebeveyn Kariyer Uyumu Ölçeği'nin (Sawitri vd., 2012) geçerlik ve güvenirliğinin Türkiye'deki ergen öğrenciler üzerinde incelenmesidir. İlk olarak ölçeği oluşturan maddeler Türkçeye uyarlanmıştır. Türkçeye uyarlanan maddeler psikolojik danışma ve rehberlik, ölçme ve değerlendirme ve Türkçe alanlarından uzmanlar tarafından incelenmiş, alınan dönütler kapsamında gerekli düzenlemeler yapılmıştır. Ölçeğin Türkçe formu Ankara il merkezinde üçü lise, üçü ortaokul düzeyinde olmak üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Social norms and parental expectations are also highly involved in children's career choices. Moreover, being economically dependent on parents in academic life may also affect their preferences (Bacanlı et al, 2013;Bacanlı et al, 2018). Although students may perceive their DoS levels to be high in different areas of their lives, they may tend to meet the expectations of their family of origin more regarding career adaptability in the current sample.…”
Section: Dos To Career Adaptability (Hypothesis 1)mentioning
confidence: 91%
“…Social norms and parental expectations are also highly involved in children's career choices. Moreover, being economically dependent on parents in academic life may also affect their preferences (Bacanlı et al, 2013;Bacanlı et al, 2018). Although students may perceive their DoS levels to be high in different areas of their lives, they may tend to meet the expectations of their family of origin more regarding career adaptability in the current sample.…”
Section: Dos To Career Adaptability (Hypothesis 1)mentioning
confidence: 91%
“…This research highlights that parents can have both positive and negative effects on their children's career development, depending on their own attitudes and behaviours (Bacanli et al, 2018;Gati & Saka, 2001;Noack et al, 2010). For instance, Lent et al (2000) suggested that parents who share their own knowledge and experiences with their children, give advice regarding their future career, and support and encourage them verbally play a significant role in the development of their career-related self-efficacy beliefs.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, no research in Turkey has focused on data collection instruments used to obtain data about these issues. Although some instruments assessing parental support have either been developed (Ş eker & Kaya, 2018) or adapted (Bacanli et al, 2018;Gu¨nes¸, 2015;€ Ozu¨nlu¨& Bacanli, 2015), there are no measures for collecting data about parents' perception of their support for their children's career development.…”
Section: Introductionmentioning
confidence: 99%
“…Türkiye'de yapılan araştırmalarda ailenin ergenlerin meslek seçiminde önemli bir etkiye sahip olduğunu ortaya koymaktadır (Bacanlı, Akyol, Kaynak ve Özhan, 2018;Özünlü ve Bacanlı, 2015). Çocuğun ya da ergenin kariyer seçiminde ailenin etkisine daha derinlemesine bakıldığında aile içi ilişkilerin, ebeveynlerin sosyoekonomik durumunun ve destek düzeyinin, ebeveynlerin karar sürecine olumlu ve olumsuz müdahalelerinin yadsınamaz etkilerinden bahsetmek mümkündür (Bacanlı, Eşici ve Özünlü, 2013).…”
Section: Introductionunclassified